The role of social media and infographics in increasing cultural heritage awareness of young athletes: an experimental study - Bademci, Fikret; Halaç, Hicran Hanım (Frontiers in Psychology, 2025)
IntroductionPreserving cultural heritage and passing it on to future generations strengthens societies’ ties to their past, increases a sense of belonging, and promotes individual and societal psychological well-being. The potential role of young people, especially athletes, in cultural heritage promotion and the increasing influence of digital tools in this process offer new opportunities for the dissemination of cultural awareness in the modern age.ObjectiveThis study aims to experimentally investigate the effectiveness of a social media and infographic-based activity in the process of increasing the cultural heritage awareness levels of young athletes studying in official sports high schools affiliated to the Turkish Ministry of National Education.MethodsThe study was conducted with 210 young athletes using a one-group pre-test/post-test design. After the pre-test was administered to the participants, infographics introducing Turkey’s cultural heritage included in the UNESCO World Heritage List were shared on a specially created social media account (Instagram) and the post-test was administered after a specified period of time. The quantitative data obtained were analyzed using frequency, percentage, dependent sample t-test and one-way ANOVA tests using IBM SPSS STATISTICS 22.0 software.FindingsAs a result of the study, it was found that the implemented activity showed a statistically significant increase in the cultural heritage knowledge and awareness levels of young athletes from pre-test to post-test. There was no significant difference between the participants’ sports branches, regions of residence and grades on cultural heritage awareness in general; however, significant regional and grade differences were observed in some specific cultural heritage areas.Conclusion and recommendationsThe findings suggest that social media and infographics are a highly effective and accessible tool for raising cultural heritage awareness among young athletes. This methodology offers an innovative and psychologically effective approach to the preservation and transmission of cultural heritage to future generations, while contributing to the strengthening of young people’s cultural identity and sense of social belonging. For future studies, research that examines the psychosocial effects of digital tools in more depth and designs long-term awareness projects is recommended.